Investigation of the mathematical model of the multidimensional automatic control system with delays - Rimas, Jonas (Lietuvos matematikos rinkinys, 2002)
The mathematical model of the mutual synchronization system composed of n = 2p (p ∈ N) joined into a chain oscillators is investigated. The precise analytical expressions of the elements of the step responses matrix of the system are obtained.